'Extreme Mass Spectrometry': the role of mass spectrometry in the study of the Antarctic Environment. (22nd October 2014) - Magi, Emanuele; Tanwar, Shivani
<x xml:space="preserve">Abstract</x> A focus on the studies of the Antarctic environment that have been performed by mass spectrometry is presented herein; our aim is to give evidence of the essential role of this instrumental technique in the framework of the scientific research in Antarctica, with a comprehensive review on the main literature of the last two decades. Due to the wideness of the topic, the present review is limited to the determination of organic pollutants, natural molecules and biomarkers in Antarctica, thus excluding elemental analysis and studies on inorganic species. The work has been divided into five sections, on the basis of the considered environmental compartment: air; ice and snow; seawater, pack ice and lakes; soil and sediments; and organisms and biomarkers. Copyright © 2014 John Wiley & Sons, Ltd.